Investigation of segregated business ethics elements influence on results of service enterprises activity - Luebcke, Kristina (Business, Management and Economics Engineering, 2010)
The article deals with interaction of segregated business ethics elements with service enterprises activity. To discover the interaction, business ethics has been differentiated to segregated elements and the influence of the segregated elements for main indexes of enterprises competitiveness discovered by correlation coefficients. Effective mana-gement is inseparable from ethics. The organization of ethical training in the company cannot just “wake” ethical awareness, and also of targeted individuals to shape their activities on matter-of-fact ethical justification, as modern ethics code object principles can be implemented not only for ethical training for staff, but also involving them in the company’s code of ethics for development. The study showed that in Lithuania, so far, very few companies have their own ethic codes and employees not only do not participate in the production, but also little wise twig about their purpose. Calculations showed, that business ethics have direct impact on the corporate profits, it is clear that ethics is only an aid in order to achieve its goal. Although the overall company’s revenue per year has increased substantially, ethical behavior may in itself be evocative. The strongest influence discovered was: commitment compliance with sales results, profit growth, and installation rates of innovations; guarantee of the reliable service information about earnings; infor-mation security assurance and leadership style for company’s image. Also, some problems of implementation of business ethics at service enterprises were discovered. Article in Lithuanian. Verslo etikos elementų įtakos paslaugų įmonės veiklos rezultatams analizė